Troubadour blues [videorecording (DVD)] : a film - Weber, Tom (Thomas J.); Weber, Tom (Thomas J.); Weber, Tom (Thomas J.); Weber, Tom (Thomas J.); Case, Peter, 1954-; Smither, Chris; Gauthier, Mary; Alvin, Dave; Erelli, Mark; Starr, Garrison; Cleaves, Slaid; Speace, Amy; et al. (Tom Weber Films, 2011)
Documentary on traveling singer-songwriters keeping alive the tradition of the itinerant bluesmen and folksingers who hopped freight trains and hitched rides across Depression-era America.